Jaringan Komunikasi Dalam Penerapan Teknologi Produksi Ubi Kayu (Kasus Petani Ubi Kayu Di Desa Suko Binangun, Kecamatan Way Seputih, Kabupaten Lampung Tengah, Provinsi Lampung) - Ageng Rara Cindoswari (Institut Pertanian Bogor, 2012)
ABSTRACT In order to increase cassava production, cassava farmers need an adequate and trusted information to gain their purpose. Fulfilling their information requirement of cassava production technology, farmers establish a communication network among farmers. The objectives of this research were: (1) to describe communication network among farmers (2) to analyze the relationship between internal charactersitics of farmer and the communication network (3) to analyze the relationship between communication network and the implementation of cassava production technology. The unit of analysis were cassavas farmer. A hundred farmers were taken as sample by using sampling intact system. This research resulted several outputs i.e : (1) communication network about seeds, fertilizer, pets and diseases were radial personal network and communication network about harvest was interlocking personal network (2) there was a significant relationship between income, group involvement, mass media ownership, arable land area with local centrality. There was also a significant correlation between educational level, revenue, group involvement, mass media ownership with global centrality. (3) there was a significant relationship between local centrality, global centrality and the implementation of cassavas production technology. Keywords: Communication Network, Cassava Farmers, Implementation of Cassava Production Technology